The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s40264-013-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction associated with Second-Generation Antidepressants in Patients with Major Depressive Disorder: Results from a Systematic Review with Network Meta-Analysis

Abstract: BACKGROUND: Sexual dysfunction (SD) is prevalent in patients with major depressive disorder (MDD) and is also associated with second-generation antidepressants (SGAD) which are commonly used to treat the condition. Evidence indicates underreporting of SD in efficacy studies. SD associated with antidepressant treatment is a serious side effect that may lead to early termination of treatment and worsening of quality of life. OBJECTIVES: To systematically assess the harms of SD associated with SGAD in adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 78 publications
1
106
1
1
Order By: Relevance
“…A second meta-analysis, of 58 randomized controlled trials and five observational studies, found only minor differences between most antidepressants, although there were relative disadvantages for paroxetine and venlafaxine, and relative advantages for bupropion 70 . A systematic review of the relative efficacy and tolerability of mirtazapine and comparator antidepressants found the former to be less likely than other antidepressants to cause adverse sexual effects 71 , possibly reflecting its antagonist effects at alpha-2 adrenergic and 5-HT2C receptors 72 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…A second meta-analysis, of 58 randomized controlled trials and five observational studies, found only minor differences between most antidepressants, although there were relative disadvantages for paroxetine and venlafaxine, and relative advantages for bupropion 70 . A systematic review of the relative efficacy and tolerability of mirtazapine and comparator antidepressants found the former to be less likely than other antidepressants to cause adverse sexual effects 71 , possibly reflecting its antagonist effects at alpha-2 adrenergic and 5-HT2C receptors 72 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…If an antidepressant is prescribed, then clinicians should discuss potential adverse sexual side effects and drug-drug interactions [Dauchy et al 2013]. There is evidence that some psychotropic medications, such as selective serotonin reuptake inhibitors, serotonin norepinephrine reuptake inhibitors (SNRIs) and tricyclic antidepressants, are associated with decreased libido [Reichenpfader et al 2014], delayed orgasm [Montejo et al 2001], continence and flow dysfunction [Pollack et al 1992]. Furthermore, antidepressants that are strong CYP2D6 (cytochrome P450 2D6) inhibitors may decrease the efficacy of TAM and are relatively contraindicated [Sideras et al 2010].…”
Section: Control Of Underlying Medical Conditionsmentioning
confidence: 99%
“…1 Whereas 26% of nondepressed people report some sexual dysfunction, this number increases to 45% in people with untreated depression, and to 63% in medically treated patients with depression. 2 In addition to high levels of baseline SD in patients with depression, many antidepressant medications independently cause SD in any or all phases of the sexual response cycle, including libido, arousal, orgasm, and ejaculation.…”
mentioning
confidence: 99%
“…2 In addition to high levels of baseline SD in patients with depression, many antidepressant medications independently cause SD in any or all phases of the sexual response cycle, including libido, arousal, orgasm, and ejaculation. 1 …”
mentioning
confidence: 99%